Ефективне одержання водню в паровому риформінгу етанолу на феритних каталізаторах - Dolgikh, L.Yu.; Stolyarchuk, I.L.; Staraya, L.A.; Vasylenko, I.V.; Pyatnitsky, Y.I.; Strizhak, P.E. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2020)
Steam reforming of ethanol is considered nowadays to be attractive mode of production of hydrogen as the most viable energy carrier for the future. Additionally, producing hydrogen from ethanol steam reforming would be environmentally friendly. Ethanol can be prepared from agricultural residues and hence is a renewable resource. Its producing from biomass fermentation is enough simple and cheap way. Besides operating conditions, the use of catalysts plays a crucial role in hydrogen production through ethanol re-forming. Different catalysts have been used for the steam reforming of ethanol, in the great majority of cases, supported noble metals, nickel and cobalt. The present work is devoted to investigation of the ethanol steam reforming over ferrites as novel oxide type of catalysts for this reaction. The ferrite catalysts, MFe2O4 (M = Mg, Mn, Fe, Zn), have been prepared by coprecipitation method; to characterize the catalysts, the methods of X-ray diffraction, electron diffraction, BET, temperature programmed desorption of CO2, the thermal gravimetry have been used. The catalytic experiments have been per-formed at atmospheric pressure in the temperature range 573-823 K. The main reaction products were acetaldehyde, acetone, CO2 and H2. It is important to note, that CO, which is undesirable impurity in hydrogen, was not appeared in the reaction products. At relatively low temperatures, high selectivity for acetone (71.3 %), that is very close to its theoretical value (75 %), was observed for FeFe2O4. Thus, the FeFe2O4 ferrite can be con-sidered as an efficient catalyst for the direct conversion of ethanol to acetone. At higher temperatures, selectivity to acetone decreases due to acetone conversion to CO2 and the target product H2. The selectivity to hydrogen increases up to 823 K for all investigated ferrites. Maximum hydrogen yield (83.4 %) was achieved for MnFe2O4, therefore it is a promising object for further study.